A Comprehensive Analysis of The Automation Adaptation Technology for Power Detection Equipment based on Unmanned Aerial Vehicles, Ranging From Infrared Temperature Measurement to Intelligent Defect Recognition - Chen, Jiaying (International Journal of Mechanical and Electrical Engineering, 2026)
This paper systematically studies the automation adaptation technology of power detection equipment based on unmanned aerial vehicles, with a focus on the full-process technical implementation from infrared temperature measurement to intelligent defect identification. This paper first reviews the development of unmanned aerial vehicle (UAV) technology, the evolution of power detection technology, and the current research status of automation adaptation technology. Secondly, the composition and functions of the unmanned aerial vehicle (UAV) power detection equipment was elaborated in detail, and the principles of infrared temperature measurement (including the basic principles of infrared thermal imaging) and intelligent defect recognition (covering defect feature extraction and classification methods) were analyzed in depth. At the technical implementation level, the software system development plan was focused on, including key links such as the selection of the operating system. The accuracy of the temperature measurement data was verified through infrared temperature measurement experiments, and the performance of the automation adaptation was systematically tested. The test results show that the technical solution can effectively improve the efficiency and accuracy of power detection. Finally, this paper summarizes the research results and practical application value, points out the deficiencies of the existing technology, and looks forward to the future research direction. This study provides important technical references and practical guidance for the intelligent application of unmanned aerial vehicles (UAVs) in power line inspection.